2011
DOI: 10.1590/s1516-18462011005000084
|View full text |Cite
|
Sign up to set email alerts
|

Dispnéia em indivíduos com asma, rinite alérgica e respiração oral

Abstract: OBJETIVO: avaliar a presença de dispnéia durante atividades físicas, de fala e sua associação. MÉTODO: a população alvo foi composta de 24 indivíduos com diagnóstico médico prévio de asma, rinite alérgica e respiração oral, onde aplicou-se oralmente em cada individuo o Questionário de Dispnéia traduzido por Cukier (1998), composto por 30 questões que permitiu a quantificação da dispnéia em atividades de fala, físicas e associadas. RESULTADOS: pela análise do questionário verificou-se maior freqüência da dispné… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…According to the processes occurring during speech production, it was possible to observe more distortions and lingual interpositions in the Research Group (RG). The obtained results corroborate data from other studies 6,24 , which identified the prevalence of the same processes claimed by the authors for impairing the stomatognathic system. According to the literature, hypertrophic palatine tonsils occupy the greatest part of the posterior portion in the oral cavity, thus influencing in the cases of lingual interposition/frontal lisp 22 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…According to the processes occurring during speech production, it was possible to observe more distortions and lingual interpositions in the Research Group (RG). The obtained results corroborate data from other studies 6,24 , which identified the prevalence of the same processes claimed by the authors for impairing the stomatognathic system. According to the literature, hypertrophic palatine tonsils occupy the greatest part of the posterior portion in the oral cavity, thus influencing in the cases of lingual interposition/frontal lisp 22 .…”
Section: Discussionsupporting
confidence: 91%
“…It is worth analyzing that the full acquisition of Brazilian Portuguese language occurs around five years of age 19 . The current study assessed children between five and 12 years of age, and did not evidence any statistical differences by relating mean age to speech production, similar to what is found in literature 6 . Regarding the association between alterations in speech sound production and gender, the study verified male prevalence.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…One of the most recurrent infections is rhinitis, which can affect up to 20% of the general population. During data collection, a lot of subjects presented airways deviation, which can be considered a bias in the survey, since this obstruction can cause impairment of vocal emission 1,21,22 .…”
Section: Resultsmentioning
confidence: 99%